Tax Incentive Policy for Geothermal Development: A Comparative Analysis in ASEAN - Abidin, Mohammad Zainul; Rosdiana, Haula; Salomo, Roy Valiant (International Journal of Renewable Energy Development, 2020)
This paper examines tax incentive policies in geothermal industries in ASEAN to better understand the development of geothermal industry investment in the ASEAN Member States (AMS) using a qualitative method. The results indicate that tax incentive policies have supported the investment climate and the development of geothermal industries in the AMS. Geothermal investments and production capacities in AMS have increased significantly. AMS that provide geothermal tax incentives include Indonesia, Lao PDR, the Philippines, Thailand and Vietnam. The performance of geothermal tax incentive policies is reflected in the level of utilization of geothermal potential, which is higher in states that provide greater tax incentives. The results also indicate that geothermal power plants in AMS use dry steam, flash and binary cycle technologies with flash plants being the most common. Results suggest that the future development of geothermal energy in AMS will be related to the tax incentive policy and investment climate in those states. Furthermore, the granting of various types of tax incentives should be focused on the initial investment in geothermal development. Â©2020. CBIORE-IJRED. All rights reserved